ATTITUDE TOWARDS TRADITIONAL, COMPLEMENTARY AND ALTERNATIVE MEDICINES (T&CAM) AND ITS USE AMONG WOMEN DURING ANTENATAL AND POSTNATAL PERIOD - Basanta Kumar Mohanty; Siti Fatimah binti Muhammad Nor; Andek Noor Faaezah binti Mohd Sadek; Saw Ohn Mar (Asian Journal of Medicine & Health Sciences, 2020)
Aim: This study investigated women’s attitude towards the use of traditional complementary and alternative medicine (T&CAM) during pregnancy and postnatal period and their practices of T&CAM during that period and its association with socio-demographic variables. Methodology: A cross-sectional descriptive study conducted among antenatal and postnatal clinic attenders at MCH clinic of Klinik Kesihatan Manjoi. Data were collected by using structured prevalidated questionnaire. Result: Out of total 103 respondents, 66.02% were antenatal and 33.98% were postnatal women with the mean age of 29.72 years. Prevalence of T&CAM among the participants was 25.24%. T&CAM use was not prevalent among pregnant or breast feeding mothers (p